2019
DOI: 10.3892/ol.2019.11234
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑519 inhibits hypoxia‑induced tumorigenesis of pancreatic cancer by regulating immune checkpoint PD‑L1

Abstract: Pancreatic cancer is highly prevalent and exhibits a high incidence and mortality rate. Hypoxia contributes to tumorigenesis and the progression of pancreatic cancer. To the best of our knowledge, the role of microRNA (miR)-519 has not been investigated in hypoxia-induced pancreatic cancer progression. The purpose of the present study was to elucidate the mechanism underlying miR-519-mediated regulation of pancreatic cancer progression. Reverse transcription-quantitative PCR and western blotting were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…Figure 3 depicts the effects of microenvironmental remodeling on PC progression under hypoxic conditions. [104] miR-142 Down miR-142-HIF-1α-vimentin, VEGF-C, E-cadherin Inhibits proliferation, EMT, and invasion [184] miR-150 Down miRNA-150-CXCR4 Inhibits migration and invasion [185] miR-519 Down miR-519-PD-L1 Inhibits cell invasiveness, and induces apoptosis [186] miR-548an Down HIF-1α-HDAC1-miR-548an-vimentin Inhibits the proliferation and invasion [187] Pathological angiogenesis under hypoxia…”
Section: Emt Invasion Migration and Metastasis Under Hypoxiamentioning
confidence: 99%
“…Figure 3 depicts the effects of microenvironmental remodeling on PC progression under hypoxic conditions. [104] miR-142 Down miR-142-HIF-1α-vimentin, VEGF-C, E-cadherin Inhibits proliferation, EMT, and invasion [184] miR-150 Down miRNA-150-CXCR4 Inhibits migration and invasion [185] miR-519 Down miR-519-PD-L1 Inhibits cell invasiveness, and induces apoptosis [186] miR-548an Down HIF-1α-HDAC1-miR-548an-vimentin Inhibits the proliferation and invasion [187] Pathological angiogenesis under hypoxia…”
Section: Emt Invasion Migration and Metastasis Under Hypoxiamentioning
confidence: 99%
“…Application of miR-519 inhibited invasiveness and tumor growth as well as induced apoptosis of pancreatic cancer in a mouse model [40].…”
Section: Discussionmentioning
confidence: 97%
“…Enhancing the expression of miR-519 appears to sensitize pancreatic cancer cells to apoptosis and inhibits their proliferation and migration. This miR prevents the activation of programmed death ligand 1 (PD-L1), under hypoxic conditions to suppress tumorigenesis [ 74 ]. In all, various studies have shown that miRs are efficient upstream mediators that target various molecular pathways.…”
Section: Micrornasmentioning
confidence: 99%
“…In all, various studies have shown that miRs are efficient upstream mediators that target various molecular pathways. Enhancing the expression of tumor suppressor miRs may prove to be an advantageous strategy and extensive research is currently being performed to exploit this strategy [ 74 , 75 , 76 , 77 , 78 ]. Conversely, oncogenic miRs are able to elevate the malignancy and proliferation of cancer cells and are associated with poor prognosis.…”
Section: Micrornasmentioning
confidence: 99%